The system of Russian cases in the aspect of Uzbek language interference: diagnosing difficulties and methods of correction - Erkinova, Asila Bakhramovna; Azizova, Nasiba Bakhritdinovna (The Lingua Spectrum, 2026)
The article addresses the problem of mastering Russian cases by Uzbek students under conditions of cross-linguistic interference. A contrastive analysis of the case systems of Russian (flexive type) and Uzbek (agglutinative type) languages is carried out, identifying the main zones of divergence. Based on an experimental study (n=80, levels A1–A2), a typology of typical case errors is presented, and the interference coefficient for each case is calculated. A methodological correction system has been developed and tested, including contrastive exercises, visual aids (fishbone, mind-map, color tables), a functional-semantic approach, and communicative games. The experimental results showed a reduction in the number of case errors in the experimental group by 62.8% versus 30.0% in the control group, proving the effectiveness of the proposed methodology.